Genetic analysis of trends in birth weight in Sahiwal Cows maintained in Chhattisgarh - Parveen, Kaiser; Singh, Mohan; Singh, Umesh; Raja, T V; Mukherjee, Kishore; Barwa, Deepti Kiran (Indian Journal of Dairy Science, 2022)
The present study was conducted on birth weight records of 841 Sahiwal calves maintained at Bull Mother Experimental Farm, College of Vety. Science and Animal Husbandry, Anjora, Durg over 20 years (2001â€“2020) to study the effect of genetic and non-genetic factors on birth weight to estimate genetic parameters and the genetic trend. The effect of genetic and non-genetic factors like sire, parity of dam, period of birth, season of birth/calving, and sex on normalized birth weight records was assessed by GLM function of WOMBAT statistical software. Mixed Model DFREML function of WOMBAT Statistical Software was used to estimate the heritability. Phenotypic trend per year was estimated as the linear regression of the phenotypic value (P) on time (year).The genetic trend were estimated by BLUP Animal Model method. The effect of sire, parity of dam, period of birth, season of birth/calving, and sex was significant for birth weight. The heritability estimate was 0.15±0.08. The estimate of phenotypic trend was -0.105±0.0.02 days/year. The estimate of genetic trend was positive (0.008±0.0.02 days/year) exhibiting positive genetic improvement in the trait. The birth weight is the most neglected parameters though it is a novel trait of increasing economic importance, because birth weight of a calf can indicates life time performance of heifers, adult cows and bulls. Thus dairy genetic improvement programmes needed to be redesign appropriate strategies that would be more beneficial to the currently changing scenarios.